Structure-Function Studies of Ser-289 in the Class C β-Lactamase from Enterobacter cloacae P99 - Trépanier, Sonia (American Society for Microbiology, 1999)
Site-directed mutagenesis of Ser-289 of the class C β-lactamase from Enterobacter cloacae P99 was performed to investigate the role of this residue in β-lactam hydrolysis. This amino acid lies near the active site of the enzyme, where it can interact with the C-3 substituent of cephalosporins. Kinetic analysis of six mutant β-lactamases with five cephalosporins showed that Ser-289 can be substituted by amino acids with nonpolar or polar uncharged side chains without altering the catalytic efficiency of the enzyme. These data suggest that Ser-289 is not essential in the binding or hydrolytic mechanism of AmpC β-lactamase. However, replacement by Lys or Arg decreased by two- to threefold the k(cat) of four of the five β-lactams tested, particularly cefoperazone, cephaloridine, and cephalothin. Three-dimensional models of the mutant β-lactamases revealed that the length and positive charge of the side chain of Lys and Arg could create an electrostatic linkage to the C-4 carboxylic acid group of the dihydrothiazine ring of the acyl intermediate which could slow the deacylation step or hinder release of the product.